Flavor constraints for a vector-like quark of Nelson-Barr type - A. L. Cherchiglia (SpringerOpen, 2021)
Abstract The Nelson-Barr (NB) mechanism to solve the strong CP problem assumes CP conservation, arranges vanishing θ ¯ $$ \overline{θ} $$ at tree-level and requires vector-like quarks (VLQs) to transmit the CP breaking to the SM. We analyze the flavor constraints coming from the presence of one such down type VLQ of NB type by performing a global fit on the relevant flavor observables. A comparison is made to the case of one generic VLQ. We find that the allowed parameter space for the VLQ Yukawa couplings and the mixing to the SM are confined to a region much smaller than in the generic case, making the NB case falsifiable in principle.